Sturge-Weber syndrome presenting with intractable seizures - Roka, Y.B.; Puri, P.R.; Ahmed, W.S.; Bista, B.K. (Journal of Institute of Medicine Nepal, 2010)
Sturge-Weber syndrome (SWS) also known as encephalotrigeminal angiomatosis is one of the many neurocutaneous syndromes consisting of port wine stain (facial nevus flammeus), congenital glaucoma and cortical calcification with anomalous leptomeningeal venous plexus. A child with intractable seizures, facial port wine stain and occipital cortical calcification is presented in this case report